Agent-based simulation in management and organizational studies: a survey. Issue 3 (2nd October 2017) - Gómez-Cruz, Nelson Alfonso; Loaiza Saa, Isabella; Ortega Hurtado, Francisco Fernando
Abstract : Purpose: The purpose of this paper is to provide a comprehensive survey of the literature about the use of agent-based simulation (ABS) in the study of organizational behavior, decision making, and problem-solving. It aims at contributing to the consolidation of ABS as a field of applied research in management and organizational studies. Design/methodology/approach: The authors carried out a non-systematic search in literature published between 2000 and 2016, by using the keyword "agent-based" to search through Scopus' business, management and accounting database. Additional search criteria were devised using the papers' keywords and the categories defined by the divisions and interest groups of the Academy of Management. The authors found 181 articles for this survey. Findings: The survey shows that ABS provides a robust and rigorous framework to elaborate descriptions, explanations, predictions and theories about organizations and their processes as well as develop tools that support strategic and operational decision making and problem-solving. The authors show that the areas that report the highest number of applications are operations and logistics (37 percent), marketing (17 percent) and organizational behavior (14 percent). Originality/value: The paper illustrates the increasingly prominent role of ABS in fields such as organizational behavior, strategy, human resources, marketing and logistics. To-date, this is the most complete survey about ABS in all management areas.